DEVELOPMENT OF ORAL SPEECH IN ENGLISH LANGUAGE - Akramaliyeva Bakhtigul (Journal of new century innovations, 2022)
Abstract: This article aims to increase the interest of students of general Secondary School in the English language and to give them insight in simple ways as well as to make effective use of visual aids. Current research provides extensive explanation in terms of the development of speech perception and perceptual learning.